A SEEG study of ERP in motor and premotor cortices and in the basal ganglia - Rektor, I; Kaiiovský, P; Bares, M; Brázdil, M; Streitová, H; Klajblová, H; Kuba, R; Daniel, P (Clinical neurophysiology, 2003)
OBJECTIVE: Our intention was to study the electrical activity related to the cognitive processing of simple sensory stimuli in the brain structures that participate in motor control. We focused our interest on the 250-600 ms time window, in which cognitive activity most probably provides the basis for the activity recorded. METHODS: Intracerebral stereoelectroencephalography (SEEG) recordings were made from 15 epilepsy surgery candidates. We studied potentials that were recorded in a time window in which P300 usually could be recorded on the scalp and that were directly recorded from brain structures involved in motor control: the primary motor cortex (MC, Brodmann's area 4); the lateral and mesial (SMA) premotor cortices (Brodmann's area 6); and the basal ganglia. We evaluated the first distinctive potential to occur in the 250-600 ms time window that displayed an amplitude gradient in several adjacent contacts. Four protocols were performed: an auditory oddball (aP3); a visual oddball (vP3); and contingent negative variation (CNV) protocols, in which the potentials evoked by the auditory warning (aCNV) and visual imperative (vCNV) stimuli were evaluated. In the protocols aP3, vP3, and vCNV, the tested person responded by flexing his/her thumb or hand. In the aCNV paradigm, and in a further auditory oddball paradigm (aP3c), no motor response was required. We compared the presence of an event-related potential (ERP) with an amplitude gradient to the absence of a generator. RESULTS: The frequency of P3-like potential components was statistically significantly higher in the basal ganglia when compared with the explored cortical sites. Statistically non-significant latency differences between the basal ganglia and the cortex were displayed. The differences in the distribution of the potentials in the individual cortical areas were insignificant. The mean latency of vP3 was longer than the latencies of aP3, aP3c and vCNV. There was no significant difference between the distribution and latency of aP3 and aP3c. CONCLUSIONS: (1) ERPs are generated in cortical as well as in subcortical structures. (2) The cognitive processing of sensory information in all the tested protocols occurred in the basal ganglia; the occurrence in the investigated cortical areas was less frequent and more dependent on the task. The basal ganglia may play an integrative role in cognitive information processing, in motor and non-motor tasks.
Keywords: reakční čas; Evoked Potentials, Visual; kognitivní evokované potenciály P300; Electroencephalography; zrakové evokované potenciály; Male; bazální ganglia; Adolescent; elektroencefalografie; Adult; Reaction Time; dospělí; mužské pohlaví; motorické korové centrum; sluchové evokované potenciály; mladiství; Event-Related Potentials, P300; Evoked Potentials, Auditory; kognice; lidé; Motor Cortex; ženské pohlaví; Basal Ganglia; Humans; Female; Cognition